PENGARUH PENERAPAN MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS III SD - Qariza, Sara; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to analyze the effect of the application of picture and picture models to the narrative writing skills of third grade students at SDN 10 East Pontianak. The method used is the experimental method, a form of research Quasi Experimental Design, with the type of Non-Equivalent Control Group Design. The population in this research is all third grade students consisting of 93 students. The research sample consisted of class III A as a control class and III B as an experimental class. The data collection tool used was a form essays with two questions. Based on data analysis, the average post-test results of the experimental class were 61,76 while the average post-test results of the control class were 56,92. The results of the t-test are obtained tcount of 2,768 and ttable Î± = 5% (dk = 29 + 26 - 2 = 53) of 1,676. Because tcount (2,768)> ttable (1,676), Ha is accepted. From the results of the calculation of the effect size obtained is 0,55 (medium criteria). This means that the application of picture and picture models have a good influence on the narrative writing skills of third grade students at SDN 10 East Pontianak.Â Keywords: Picture and Picture Models, Writing Skills, NarrativeÂ